Adenovirus Isolated From a Cat Is Related to Human Adenovirus 1 - Ongrádi, Joseph; Chatlynne, Louise G.; Tarcsai, Katalin Réka; Stercz, Balázs; Lakatos, Béla; Pring-Åkerblom, Patricia; Gooss, Donald; Nagy, Károly; Ablashi, Dharam V. (Frontiers in Microbiology, 2019)
An adenovirus (AdV) has been isolated from the rectal swab of a domestic cat (Felis catus) and named feline adenovirus (FeAdV) isolate. It replicates and causes cytopathological effects in many human, feline, other mammalian cell lines that have both Coxsackie-adenovirus-receptor and integrins. Its antigens cross-react with anti-human adenovirus antibodies in immunofluorescence and immunocytochemistry assays. Electron microscopy revealed typical extracellular icosahedral particles and pseudo arrays inside cells. Sequence analysis of hexon and fiber genes indicates that this virus might belong to human adenovirus (HAdV) C species and might be a variant of type 1. In the fiber protein, three altered amino acids occur in the shaft; four altered residues are found in the knob region as compared to a European human adenovirus might be type 1 isolate (strain 1038, D11). One alteration affects amino acid 442 forming an RGS motif in an alanine rich region that might be an alternative way to bind integrins with subsequent internalization. Substitutions in the hexon sequence are silent. As compared to published human adenovirus sequences, the fiber is related to the original American prototype and recently described Taiwanese human adenovirus 1 isolates, but the hexon sequences are related to adenovirus isolates from France, Germany, Japan, and Taiwan. Serology carried out on FeAdV infected M426 cells indicates a prevalence of IgG in 80% of domestic cats in Delaware, USA. FeAdV isolate seems to be a recently recognized virus with possible pathogenic effects and, simultaneous human and feline infections are possible. Further molecular and biological characterization of this feline adenovirus isolate, as well as studies on both human and feline epidemiology and pathomechanisms, especially in endangered big cats, are warranted. FeAdV might have further practical advantages. Namely, it could be utilized in both human and feline AIDS research, developed into diagnostic tools, and gene therapy vectors in the near future.